Administration of Drugs for Pharmacotherapy of Tuberculosis According to GSP Requirements - Osyntseva, Alina (SSP Modern Pharmacy and Medicine, 2024)
This research paper outlines the findings from a comprehensive investigation focused on the dispensation and management of antituberculosis medications in pharmaceutical practices. The examination of antituberculosis medications was conducted using various classification systems, including ATC codes, clinical and pharmacological, classification and legal, nomenclature and legal groups. The study provides a detailed analysis of the harmonization process for GxP standards within Ukraine, offering a thorough understanding of the current practices. Additionally, the research looks into the supply chain dynamics of antituberculosis medication distribution. Developed within the study are strategic guidelines for the proper storage of these medications, essential for maintaining their efficacy and safety. A systematic proposal for the spatial organization of storage facilities in the wholesale sector is presented, ensuring compliance with GSP. The study’s goal was to refine the methodologies involved in the storage and management of antituberculosis drugs, with the ultimate aim of enhancing the efficiency of tuberculosis treatment protocols. This, in turn, is expected to elevate the caliber of healthcare delivery and pharmaceutical care available to patients afflicted with tuberculosis. Expanding on the study's contributions, the paper highlights the implications of these findings for public health policy and the potential to streamline pharmaceutical organization. By drawing attention to the criticality of adherence to rigorous storage protocols, the research underscores the necessity of meticulous oversight in the pharmaceutical supply chain. The insights gained from the study are not only pivotal for healthcare providers but also for policymakers tasked with the mandate of curbing the tuberculosis epidemic. The proposed recommendations provide a scaffold for future enhancements in drug management practices.